Echi della catastrofe nel Targum Yonatan dei Profeti - Poli, Eliseo (Annali di storia dell' esegesi, 2024)
This contribution aims to examine the texts of the Targum of Jonathan to the Prophets that contain explicit references to Rome, in order to verify any echoes of the catastrophe experienced in the aftermath of the destruction of Jerusalem and the failure of the Bar Kokhba revolt. The interpretation of the passages should be placed within an ideology founded on the concept of exemplarity.